PEMBERDAYAAN MASYARAKAT MELALUI INOVASI TRANSPORTASI ONLINE BERBASIS WHATSAPP DI DESA GALANG TINGGI, BANYUASIN III - Novianti, Rahmi; Pusnita, Indah; Mahdiana, Yana; Alpiansyah, Alpiansyah (Universitas Sanata Dharma, 2023)
The purpose of this activity is to socialize village transportation development innovations through WhatsApp-based online motorcycle taxis in Galang Tinggi Village, Banyuasin III. The benefit of this activity is that people's understanding of technology can be applied to village transportation needs, at least it can provide an alternative in facilitating access to accelerating the economy and continuity of community in the village. The method of implementing the activity is in two stages, coordinating with the Head of Galang Tinggi Village to obtain an overview and initial data regarding the geographic profile and conditions, village demographics and digital capabilities of community members. The second stage is implementing socialization on the use of WhatsApp social media as an information medium for online motorcycle taxis to facilitate public transportation. This activity provides knowledge and understanding as well as an enthusiastic attitude to initiate business opportunities for online motorcycle taxi transportation services. This activity is very important in efforts to achieve early progress in digital society. The hope is that people can take advantage of digital means to create business opportunities that can reach a wider market and are cost efficient.